2016
DOI: 10.1177/0363546516651441
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Characteristics and Strength of the Hamstring Muscles Remain Altered at 2 Years After Use of a Hamstring Tendon Graft in Anterior Cruciate Ligament Reconstruction

Abstract: The muscle-tendon properties of the semitendinosus and gracilis are substantially altered after harvesting, and these alterations may contribute to knee flexor weakness in the surgical limb. These deficits are more pronounced in knees with tendons that do not regenerate and are only partially offset by compensatory hypertrophy of other hamstring muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
186
9
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(214 citation statements)
references
References 30 publications
14
186
9
2
Order By: Relevance
“…The surgeon then prepares the knee and drills holes in the tibia and the femur to place the graft. Several studies have shown that hamstring grafts, involving the surgical removal of the distal ST tendon are associated with significant muscle atrophy and retraction of the muscle belly (Burks et al, 2005;Konrath et al, 2016;Nomura et al, 2015).…”
Section: Hamstring Graftsmentioning
confidence: 99%
See 4 more Smart Citations
“…The surgeon then prepares the knee and drills holes in the tibia and the femur to place the graft. Several studies have shown that hamstring grafts, involving the surgical removal of the distal ST tendon are associated with significant muscle atrophy and retraction of the muscle belly (Burks et al, 2005;Konrath et al, 2016;Nomura et al, 2015).…”
Section: Hamstring Graftsmentioning
confidence: 99%
“…A number of observational studies (Konrath et al, 2016;Nomura et al, 2015;Takeda, Kashiwaguchi, Matsuura, Higashida, & Minato, 2006) have reported decrements in concentric (Tengman et al, 2014) and eccentric (Tengman et al, 2014;Thomas, Villwock, Wojtys, & PalmieriSmith, 2013) knee flexor strength in the years following ACLR surgery in addition to reduced ST muscle size (Nomura et al, 2015) and altered BFLongHead muscle architecture (Timmins, Shield, Williams, Lorenzen, & Opar, 2015). It has been suggested that after a significant knee injury, such as an ACL injury, the biomechanics of the lower limb are altered, and these changes increase the risk of future HSI (Verrall et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations